Model Transparansi Anggaran Desa di Yogyakarta - Avina, Amalia Wizrotul (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan Bandung, 2023)
Abstract Law No. 6/2014 on Villages states that villages have the authority to govern and realize the implementation of development in an effort to maximize the quality of people's welfare. Good Governance is a new paradigm in the concept of good governance, including village government, which emphasizes three aspects: transparency, accountability and participation. This research aims to find out how the village government budget transparency model in Yogyakarta. This research uses descriptive qualitative research methods. The data sources used in this research are primary data sources obtained through interviews and secondary data sources obtained from books, journals, articles, websites and related documents. The informants used were the village head, village secretary and village government staff. Data analysis used the Miles and Huberman model, namely data reduction, data display, and conclusion drawing. In Tamanmartani Village, budget transparency is achieved through village meetings and the use of the SISKEUDES application so that the public can access financial information online. Selomartani village also utilizes billboards and a website to ensure transparency. The involvement of village officials and the village council promotes accountability. The implementation of this transparency model is not politically driven, but rather a requirement and a means for the community to understand how funds are used. Keywords: Transparency, Good Governance, Political Strategy